Scalar bosons in minimal and ultraminimal technicolor: Masses, trilinear couplings, and widths - Doff, A.; Natale, A. A. [UNESP] (American Physical Society (APS), 2010)
We compute masses, trilinear self-couplings, and decay widths into weak bosons of the scalar composite bosons in the case of the minimal and ultraminimal technicolor models. The masses, computed via the Bethe-Salpeter equation, turn out to be light, and the trilinear couplings smaller than the one that would be expected when compared to a fundamental standard model scalar boson with the same mass. The decay widths into electroweak bosons of the ultraminimal model scalars bosons are much smaller than the one of the minimal model. © 2010 The American Physical Society.